The influence of referentiality, definiteness, and “preposition+determiner” contraction on relative clause processing - Bezerra, Gitanna Brito (2019)
In this paper, we present two experiments (questionnaires) that we conducted to investigate the influence of referentiality, definiteness, and preposition+determiner contraction (P+D contraction) on relative clause processing. The first experiment was conducted in Brazilian Portuguese, and the results revealed an influence of referentiality and definiteness on relative clause interpretation: N2 modification (low attachment) was more probable when N2 was referential and when it was introduced by an indefinite article. The results did not reveal, however, an effect of P+D contraction. The second experiment was conducted in Spanish and it focused on referentiality and P+D contraction. The results revealed a significant effect of both factors: N2 modification was more probable when N2 was referential and when the article preceding it was not contracted with the preposition. Based on these results, we emphasize the influence of the three factors investigated on relative clause interpretation, highlighting the novelty of the P+D contraction effect.